Response of the Biocontrol Agent Pseudomonas pseudoalcaligenes AVO110 to Rosellinia necatrix Exudate - Pliego, Clara; Crespo-Gómez, José Ignacio; Pintado Calvillo, Adrián; Pérez-Martínez, Isabel; De Vicente, Antonio; Cazorla-López, Francisco Manuel; Ramos-Rodríguez, Cayo Juan (American Society fo Microbilogy, 2019)
The rhizobacterium Pseudomonas pseudoalcaligenes AVO110, isolated by the enrichment of competitive avocado root tip colonizers, controls avocado white root rot disease caused by Rosellinia necatrix. Here, we applied signature-tagged mutagenesis (STM) during the growth and survival of AVO110 in fungal exudatecontaining medium with the goal of identifying the molecular mechanisms linked to the interaction of this bacterium with R. necatrix. A total of 26 STM mutants outcompeted by the parental strain in fungal exudate, but not in rich medium, were selected and named growth-attenuated mutants (GAMs). Twenty-one genes were identified as being required for this bacterial-fungal interaction, including membrane transporters, transcriptional regulators, and genes related to the metabolism of hydrocarbons, amino acids, fatty acids, and aromatic compounds. The bacterial traits identified here that are involved in the colonization of fungal hyphae include proteins involved in membrane maintenance (a dynamin-like protein and ColS) or cyclic-di-GMP signaling and chemotaxis. In addition, genes encoding a DNA helicase (recB) and a regulator of alginate production (algQ) were identified as being required for efficient colonization of the avocado rhizosphere.
Keywords: Agentes de control biológico de plagas; Biocontrol; Pseudomonas pseudoalcaligenes; Rosellinia necatrix; Exudate